Peran Pemerintah Nagari dalam Penanganan Pascabencana di Nagari Matua Mudiak Kabupaten Agam - Azzahra Ulhusna; Hasbullah Malau (Al-DYAS, 2026)
Post-disaster recovery at the nagari level plays an important role in ensuring the continuity of public services, the restoration of livelihoods, and the safety of affected communities. However, studies on the implementation of the nagari government’s role in post-disaster management remain limited. This study aims to analyze the role of the Nagari Matua Mudiak Government as an implementer, facilitator, and coordinator in the post-disaster rehabilitation and reconstruction process. This study employed a descriptive qualitative approach with a case study design in Nagari Matua Mudiak, Agam Regency. The research informants comprised five individuals representing the nagari government, the Disaster Preparedness Group, community leaders, volunteers, and affected residents, who were selected purposively. The data were analyzed through the stages of reduction, presentation, conclusion drawing, and verification, while data validity was assessed using source and technique triangulation. The results showed that the disaster affected 22–23 houses, displaced 593 people across 35 locations, damaged 19 road sections and 32 irrigation channels, and caused losses of at least IDR 7.415 billion. As an implementer, the nagari government recorded data on victims, managed assistance, mobilized mutual cooperation, and submitted proposals for the recovery of housing, livelihoods, and infrastructure. As a facilitator, the nagari government connected the community with government programs, donor agencies, volunteers, and technical institutions. Meanwhile, as a coordinator, the nagari government integrated information and allocated responsibilities among local actors and the regency government. Rehabilitation efforts have been implemented in the areas of basic services, logistics distribution, social support, and the restoration of access to affected areas. However, the recovery of productive economic activities, professional psychosocial services, housing assistance, and large-scale reconstruction remains constrained by inconsistent data, limited budgets and authority, damaged access routes, topographical conditions, weather-related risks, limited human resources and equipment, lengthy administrative processes, and the suboptimal dissemination of public information and provision of evacuation sites. This study confirms that effective post-disaster recovery at the nagari level requires strengthened institutional capacity, cross-sectoral coordination, data consistency, financial support, and a more integrated public information system.